Textural properties and consumer preference of functional milk puddings fortified with apricot kernel extracts. Issue 2 (19th December 2021) - Li, Dengyun; Zhang, Yifang; Jiang, Ru; He, Wenmeng
Abstract: Both the demand for functional foods and their consumption have increased rapidly in recent years. Apricot kernels, originated in China, are rich in dietary protein, fat, fiber, and exhibit high antimicrobial and antioxidant activities. The effects of the agar–gelatin ratio and milk volume on the texture of apricot kernel milk puddings were evaluated. Texture profile analysis indicated that increasing volumes of agar and milk contributed to the hardness and gumminess but reduced the cohesiveness of puddings. The pudding sample S2 (250 ml of milk, 200 ml of water, 60 g of raw apricot kernels, 30 g of sugar, 5 g of gelatin, and 2 g of agar) was ultimately determined as the essential texture matrix prototype for further development of puddings. The effects of the ratio of raw apricot kernels to roasted apricot kernels and cream content in puddings on consumer preference were determined by quantitative descriptive analysis and consumer testing. Both quantitative descriptive analysis and external preference mapping of all puddings (12 samples) indicated that the pudding sample P6 (250 ml of milk, 200 ml of water, 40 g of raw apricot kernels, 20 g of roasted apricot kernels, 40 g of cream, 30 g of sugar, 5 g of gelatin, and 2 g of agar) showed enhanced consumer acceptance. The properties driving preference for P6 were oral smoothness, overall flavor, degree of roast, and milky taste. P6 was ultimately selected as the prototype to incorporate apricot kernels for the development of functional milk puddings with fortified essential nutrients. Abstract : Apricot kernel was used as new ingredients in milk pudding. The ingredients of P6 (250 ml of milk, 200 ml of water, 40 g of raw apricot kernels, 20 g of roasted apricot kernels, 40 g of cream, 30 g of sugar, 5 g of gelatin, and 2 g of agar) showed enhanced consumer acceptance. P6 was ultimately selected as the prototype to incorporate apricot kernels for the development of functional milk puddings with fortified essential nutrients.